Comparative and chemometric analysis of correlations between the chemical fingerprints and anti‐proliferative activities of ganoderic acids from three Ganoderma species. Issue 4 (1st April 2019) - Zhang, Chunyun; Fu, Dan; Chen, Guilin; Guo, Mingquan
Abstract: Introduction: Investigation on ganoderic acids (GAs) from different cultivars and origins of Ganoderma species, regarding to their composition, contents and bioactivities, will be of great importance for the development and quality control of Ganoderma ‐based healthcare products or drugs. Objective: Comparative and chemometric analysis of different Ganoderma species were conducted to reveal the correlations between their chemical fingerprints and anti‐proliferative activities. Methodology: Six Ganoderma samples with different origins and parts of fruiting body (pileus and stipe) were extracted with chloroform and enriched by a SPE‐C18 cartridge. The eluents were used for high‐performance liquid chromatography ultraviolet electrospray ionisation tandem mass spectrometry (HPLC‐UV/ESI‐MS/MS) analysis and cytotoxicity assay with three cancer cell lines (SGC‐7901, HT‐29 and Hep G2). Chemometric analysis was applied to correlate their chemical compositions and corresponding bioactivities. Results: Sixteen peaks (accounting for 70% of the total peak areas) were identified as GAs, and their contents ranged from 0.368 to 10.8 μg/g in various Ganoderma species. The extracts from three Ganoderma species had significant anti‐proliferative activities (inhibitory rates ranged from 70.8% to 80.7%), and extracts from Lurongzhi showed remarkable inhibition to all three cancer cells (inhibitory rates range from 81.6% to 92.1%). Finally, chemometric analysis revealed that 3, 7, 12‐trihydroxy‐4, 4, 14‐trimethyl‐11, 15‐dioxochol‐8‐en‐24‐oic acid and 12‐acetoxy‐15‐hydroxy‐4, 4, 14‐trimethyl‐3, 7, 11‐trioxochol‐8‐en‐24‐oic acid were the two compounds with most potential anti‐proliferative activity for SGC‐7901. Conclusion: The correlations between chemical fingerprints and anti‐proliferative activities of various Ganoderma species give remarkable insight into the true bioactive components of chemical markers for the quality assessment of the Ganoderma resources, and provide a good guidance for the study on the chemical spectrum–bioactivity relationship. Abstract : Ganoderic acids from six Ganoderma samples have been analyzed using HPLC‐UV‐ESI‐MS/MS. Anti‐Proliferative activities of the Ganoderma extracts were performed on three cancer cell lines. Specific anti‐proliferative compounds in the Ganoderma extracts have been revealed.